AFVIGELSE OG PERSONOPFATTELSER - Kolind, Torsten (Tidsskriftet Antropologi, 2007)
The article offers an analytical framework for studying deviance. Research in deviance is relatively sparse in anthropology, by linking up with analysis of different societies’ perceptions of the person, however, it is possible to develop a model for understanding different ideal typical responses to deviant acts. On the one hand we have an idea of the person, which strongly relates acts to the individual, and with a high focus on individual responsibility, on the other end of the continuum act are interpreted as reflections and statements of social relations beyond the single individual. As a consequence of these differences the nature of deviance is perceived in dissimilar ways. In short, one the one hand, deviance is explained by reference to the individual person and strategies of normalisation and integration is pursued. On the other hand deviance is explained extra-personally and strategies of re-categorisation or elimination are developed. The article offers contemporary examples from the author’s studies of respectively punishment and substance abuse treatment.